Answer: y = 8x
Step-by-step explanation:
Answer:
(4,12)
(-1,-3)
Step-by-step explanation:
x^2 - y = 4
y = 3x
Use substitution. Substitute 3x for y in the first equation
x^2 - (3x) = 4
x^2 -3x =4
Subtract 4 from each side
x^2 -3x -4 = 4-4
x^2 -3x-4 =0
Factor
(x-4) (x+1) =0
Using the zero product property
x-4 =0 x+1 =0
x=4 x=-1
Now to find y for each x solution
x=4
y =3x = 3(4) =12
(4,12)
x=-1
y =3x = 3(-1) =-3
(-1,-3)
Add the minutes it takes per book:-
1.2 + 0.8 = 2
You spend 2 minutes reading!
Answer:
0.8 ounces each student
Step-by-step explanation:
You divide 4 by 5 and get your response.